1999
DOI: 10.1038/sj.onc.1202622
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide-induced killing of normal and malignant human lymphocytes is by a non-apoptotic mechanism

Abstract: Synthetic ceramides induce apoptotic death of Jurkat and HL60 leukaemia cell lines. By contrast we show here that ceramide induces non-apoptotic killing of malignant cells from patients with B-chronic lymphocytic leukaemia (B-CLL) and of normal B lymphocytes. The protein phosphatase inhibitor okadaic acid readily induces apoptosis of B-CLL cells, indicating that this death pathway is fully functional in these cells. The ability of ceramide to activate the apoptotic protease caspase 3 in HL60 cells but not in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 41 publications
1
32
0
2
Order By: Relevance
“…Ceramide, which can be generated through either de novo synthesis or via acid hydrolysis of sphingomyelin (73), has been established as an inducer of apoptosis in neoplastic cells, including those of hematopoietic origin (43). In this regard, induction of apoptosis in leukemic cells by ara-C has been associated with increased ceramide levels (42), and of particular relevance to the present studies, ceramide generation has been implicated in the lethal actions of F-ara-AMP in B-chronic lymphocytic leukemia cells (44,74). Furthermore, it has been shown that perturbations in ceramide metabolism can enhance the sensitivity of tumor cells to conventional cytotoxic drugs (75).…”
Section: Discussionmentioning
confidence: 87%
“…Ceramide, which can be generated through either de novo synthesis or via acid hydrolysis of sphingomyelin (73), has been established as an inducer of apoptosis in neoplastic cells, including those of hematopoietic origin (43). In this regard, induction of apoptosis in leukemic cells by ara-C has been associated with increased ceramide levels (42), and of particular relevance to the present studies, ceramide generation has been implicated in the lethal actions of F-ara-AMP in B-chronic lymphocytic leukemia cells (44,74). Furthermore, it has been shown that perturbations in ceramide metabolism can enhance the sensitivity of tumor cells to conventional cytotoxic drugs (75).…”
Section: Discussionmentioning
confidence: 87%
“…It was recently reported that the killing of Jurkat cells by synthetic ceramide could occur by both apoptotic and non-apoptotic mechanisms (Mengubas et al, 1999a(Mengubas et al, , 1999b. In those studies, zVAD-fmk did not decrease the overall rate of killing of Jurkat cells by C2-ceramide, but did dramatically decrease the induction of apoptosis.…”
Section: C2-ceramide Induces Dna Fragmentation That Is Caspase-dependmentioning
confidence: 87%
“…In particular, ceramide-mediated apoptotic cell death is extensively investigated (8 -10). On the other hand, several investigations indicate that nonapoptotic cell death is induced in certain tumor or normal cells by ceramide (11)(12)(13). However, the molecular pathways underlying the latter cell death remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%